Finite element analysis on the effect of hollow section on the strength of foamed concrete beam - Chong, Beng Wei (2019)
Hollow section is introduced on beam to reduce a dead load of the structure, which can ease the usage of IBS and hence minimize construction cost. It can also act as a pathing for mechanical and electrical works. Lightweight concrete produced by replacing 30% cement with PSBE with a density of 1600 kg/m³. Processed Spent Bleaching Earth (PSBE) is a residue from an oil-refining process that can be used to replace cement in the concrete mix. The study is conducted to analyse the best shape and position of the hollow section using ANSYS software. The study will also verify the results of previous experimental studies. Four-point bending test simulated on six beams samples. Beam S1, S2 and S3 have a square opening of size 50mm while beam C1, C2, and C3 have a circular opening of 50mm diameter. Samples Number 1 has opened right on the neutral axis. Samples Number 2 has opening above neutral axis while samples Number 3 have opening below the neutral axis. The size of all six beams is 150mm x 200mm x 1500mm. Finite element analysis performed on the samples with the usage of ANSYS software. The failure load and maximum total deformation are determined. From the result, beams with circular hollow section could withstand higher loading and had smaller deflection compared to its square hollow section counterpart. Also, the best position of the hollow is located above the neutral axis, while beams with hollow below the neutral axis were the weakest. Beam C2 produced the highest load among all sample, which was 4.015kN. The lowest beam was S3, which failed at 3.338kN. For beams with square hollow section, the beam produced a 1% increase in loading when the hollow section was above the neutral axis, but a strength loss of 15.3% observed when the hollow section was below the neutral axis. For beams with circular section, the hollow section above the neutral axis produced a 0.65% increase in loading, while the hollow section below neutral axis caused a strength loss of 3.79%. The resulting pattern agreed with experimental results. Concrete is weak in tension, so in unreinforced beams, the beam loses significant strength when the hollow section is below the neutral axis, which is the tension zone. Shifting the hollow section to above neutral axis strengthened the beams because concrete is good in compression and hollow section at the compression zone has little effect on the performance of the beams. The research aims to provide an understanding of the best shape and position of the hollow for a foamed concrete beam. It also verifies the ability of Finite Element Analysis to predict the performance of the hollow structure in the potential full-scale study.